High use of private providers for first healthcare seeking by drug-resistant tuberculosis patients: a cross-sectional study in Yangon, Myanmar - Sucitro Dwijayana Sidharta; Jason Dean-Chen Yin; Joanne Su-Yin Yoong; Mishal Sameer Khan (BMC, 2018)
Abstract Background Drug resistance is a growing challenge to tuberculosis (TB) control worldwide, but particularly salient to countries such as Myanmar, where the health system is fragmented across the public and private sector. A recent systematic review has identified a critical lack of evidence for local policymaking, particularly in relation to drivers of drug-resistance that could be the target of preventative efforts. To address this gap from a health systems perspective, our study investigates the healthcare-seeking behavior and preferences of recently diagnosed patients with drug-resistant tuberculosis (DR-TB), focusing on the use of private versus public healthcare providers. Methods The study was conducted in ten townships across Yangon with high DR-TB burden. Patients newly-diagnosed with DR-TB by GeneXpert were enrolled, and data on healthcare-seeking behavior and socio-economic characteristics were collected from patient records and interviews. A descriptive analysis of healthcare-seeking behavior was followed by the investigation of relationships between socio-economic factors and type of provider visited upon first feeling unwell, through univariate logistic regressions. Results Of 202 participants, only 8% reported first seeking care at public facilities, while 88% reported seeking care at private facilities upon first feeling unwell. Participants aged 25-34 (Odds Ratio = 0.33 [0.12-0.95]) and males (Odds Ratio = 0.39 [0.20-0.75]) were less likely to visit a private clinic or hospital than those aged 18-24 and females, respectively. In contrast, participants with higher income were more likely to utilize private providers. Prior to DR-TB diagnosis, 86% of participants took medications from private providers. After DR-TB diagnosis, only 7% of participants continued to take medications from private providers. Conclusion In urban Myanmar, most patients shifted to being managed exclusively in the public sector after being formally diagnosed with DR-TB. However, since the vast majority of DR-TB patients first visited private providers in the period leading to diagnosis, related issues such as unregulated quality of care, potential delays to diagnosis, and lack of care continuity may greatly influence the emergence of drug-resistance. A greater understanding of the health system and these healthcare-seeking behaviors may simultaneously strengthen TB control programmes and reduce government and out-of-pocket expenditures on the management of DR-TB.